TEACHING VOCABULARY THROUGH GRAMMAR- TRANSLATION METHOD - Abdurrahman Hi.Usman (Universitas Khairun, 2015)
As a traditional teaching method, Grammar-Translation Mehtod is still currently used nowadays. Although it is very suitable to teach grammar, but it is suitable for certain materials in certain places as well. One of the suitable materials is vocabulary. Vocabulary is very important all languages because there is no language without vocabulary. Every language is bulit up by the smallest meaningful unit that is called morpheme. Morphemes bulid up words, and the words listed in certain groups are called vocabulary. However, vocabulary has a very close relationship with grammar. Vocabulary is derived from morphology, and morphology is categorized grammar. Therefore, teaching vocabulary through Grammar-Translation Mehtod is possibly effective. Key words: teaching, vocabulary, words, language Grammar-Translation Mehtod